2006
DOI: 10.1590/s0100-39842006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção da xerostomia e da mucosite oral induzidas por radioterapia com uso do laser de baixa potência

Abstract: OBJETIVO: Verificar se o uso do laser de InGaAlP com comprimento de onda de 685 nm pode reduzir a incidência de xerostomia, gravidade da mucosite oral e da dor associada à mucosite em pacientes portadores de câncer de cabeça e pescoço submetidos a radioterapia. MATERIAIS E MÉTODOS: Sessenta pacientes portadores de carcinoma de cabeça e pescoço foram submetidos a radioterapia com dose diária de 1,8 a 2,0 Gy e dose final de 45 a 72 Gy. O volume salivar foi medido nos dias um, 15, ao final do tratamento e após 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
1
19
1
9
Order By: Relevance
“…12,26 The mouthwash performed with sodium bicarbonate is used due to the change caused by it in the pH of the oral cavity, making it less conducive to the growth of pathogenic microorganisms, also aids in debridement of lesions, reduced odor and saliva fluidisation. 3 As with xerostomia, the low power laser in use is indicated by mucositis stimulate cellular activity and accelerate the healing process due in part to reduced acute [17][18]27 Study found that laser therapy also significantly reduced pain, severity and duration of symptoms of mucositis in cancer patients. 28 The assessment of nutritional status is important because of the limitations caused by mucositis affecting the food, such as dysphagia, leading to secondary problems such as loss of weight, loss of appetite, anorexia and dehydration, it is important the recommendation to the patient in increasing the the fluid intake.…”
mentioning
confidence: 99%
“…12,26 The mouthwash performed with sodium bicarbonate is used due to the change caused by it in the pH of the oral cavity, making it less conducive to the growth of pathogenic microorganisms, also aids in debridement of lesions, reduced odor and saliva fluidisation. 3 As with xerostomia, the low power laser in use is indicated by mucositis stimulate cellular activity and accelerate the healing process due in part to reduced acute [17][18]27 Study found that laser therapy also significantly reduced pain, severity and duration of symptoms of mucositis in cancer patients. 28 The assessment of nutritional status is important because of the limitations caused by mucositis affecting the food, such as dysphagia, leading to secondary problems such as loss of weight, loss of appetite, anorexia and dehydration, it is important the recommendation to the patient in increasing the the fluid intake.…”
mentioning
confidence: 99%
“…(Parulekar et al, 1998;Raber-Durlacher, 1999;Abreu;Silva, 2000;Raber-Durlacher, 2000;Cardoso et al, 2005;Jham;Freire, 2006;Rubira et al, 2007;Santos et al, 2009). Revisões sistemáticas e ensaios clínicos recentes identificaram intervenções potencialmente efetivas para a prevenção e redução da gravidade da mucosite que incluem: adequação do meio bucal, anestésicos tópicos, colutórios à base de povidona ou digluconato de clorexidina (anti-sépticos), glutamina oral (manutenção do sistema imunológico), uso tópico de mel (propriedades antimicrobianas e antisépticas), maior ingestão de vitamina A e vitamina E, suplementos de aminoácidos, crioterapia (vasoconstrição), fatores de crescimento (proliferação e diferenciação de neutrófilos e macrófagos), amifostina (cito protetor), sulcrafate (tamponamento ácido e estimulador da produção de muco), antibióticos, analgésicos sistêmicos, narcóticos, antiinflamatórios, laser de baixa intensidade (Barash et al, 1995;Cowen et al, 1997;Sonis, 1998;Bensadoun, 1999;Raber-Durlacher, 1999;Silverman Junior, 1999;Biron et al, 2000;Herrstedt, 2000;Bensadoun et al, 2001;Sandoval et al, 2003;Catão, 2004;Glenny et al, 2004;Cardoso et al, 2005;Nes;Posso, 2005;Bensadoun, 2006;Harris, 2006;Lopes et al, 2006;Maya et al, 2006;Kelner;Castro, 2007;Schubert et al, 2007;Volpato et al, 2007;Abramoff et al, 2008;…”
Section: Rtunclassified
“…interromper o tratamento antineoplásico. Proporciona alívio da dor, maior conforto ao paciente, controle da inflamação, manutenção da integridade da mucosa, melhor reparação tecidual, obtendo repostas positivas do ponto de vista clínico e funcional; melhorando a qualidade de vida dos pacientes durante o tratamento oncológico (Barash et al, 1995;Cowen et al, 1997;Bensadoun et al, 1999;Bensadoun et al, 2001;Sandoval et al, 2003;Catão, 2004;Nes;Posso, 2005;Maiya et al, 2006;Bensadoun, 2006;Lopes et al, 2006;Schubert et al, 2007;Abramoff et al, 2008;Arora et al, 2008;Klastersky et al, 2008;Campos et al, 2009;Khouri et al, 2009;Kuhn et al, 2009;Moraes et al, 2009;Simões et al, 2009a;Simões et al, 2009b;Zanin et al, 2010). (Catão, 2004apud Veçoso 1 , 1993.…”
Section: Rtunclassified
See 2 more Smart Citations